Hubungan Mengonsumsi Makanan Selingan dengan Kejadian Early Childhood Caries pada Anak Usia 2-5 Tahun di Kota Padang - Retno Sri Mulyani; Susi Susi; Surma Adnan (Faculty of Dentistry Universitas Andalas, 2019)
Dental caries is one of the most common problem that can be found in both adults and children. Dental caries in primary teeth on children aged 0-71 months is known as Early Childhood Caries (ECC). Reports by Global Burden of Disease Study 2015 caries on primary teeth ranks 12th which affects as many as 560 million children worldwide. There are many predisposition factors that cause ECC, which are closely related to food consumption such as food snacking.The purpose of this study is to determine the relationship between food snacking consumption and Early Childhood Caries on children aged 2-5 years old in Padang. This study used a cross sectional design, with total sampel of 107 children aged 2-5 years in Padang. The location was selected through Stratified Random Sampling Method and samples was selected through Consecutive Sampling Method. Data was collected by using food frequency questionares and intra-oral examination that were analyzed by Chi-Square test with p<0.05. The results showed that there was a significant relationship between food snacking and ECC (p=0.000). The conclution of this study was that food snacking consumption is associated with Early Childhood Caries on children aged 2-5 years in Padang.